Use reduced track profile and discrete simulation to calculate train travel time - Fikejz, Jan; Merta, Jan (Dime University of Genoa, 2018)
This article deals about utilization of reduced track profile for dynamic calculation of train travel time. Attention is firstly aimed on the description of the location of trains in the designed model of railway network. Further attention is aimed on the design of the dynamic calculation of train travel time. This calculation utilization of computer simulation and reduced track profile as a substitute of the real track profile of substitute gradients.
Využití redukovaného profilu tratě a počítačové simulace pro výpočet čas jízdy vlaku
Keywords: Use; reduced; track; profile; discrete; simulation; calculate; train; travel; time; Využití; redukovaného; profilu; tratě; počítačové; simulace; výpočet; čas; jízdy; vlaku